Implementasi Pervasive Computing untuk Smart Bag dengan menggunakan RFID - Muhammad Yaqub; Rizal Maulana; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In this era of technology, we are required to move quickly and precisely without making a significant mistake. However, individuals who experience problems that have not been resolved in the case of negligence that causes the goods are often left behind. Many ways have been done to find a solution, one of them by writing notes about the list of goods to be carried. But this way can be troublesome and time consuming. This is where the role of Internet-based technology It is most needed to help solve the problem by developing a smart device. This system functions into several parts of hardware and software. This research uses NodeMCU as microcontroller, Wi-Fi network as connectivity at Firebase Realtime Database. Firebase is used as a communication between hardware and software to store data on read items, as well as reminders of smartphone applications. The RFID Reader sensor device will eliminate readings on the goods UID and the microcontroller will send status data of incoming and outgoing goods to Firebase for the goods already read. The LED light actuator device performs a special action for a red or green light based on the status of the goods obtained. From the results of the implementation, each item succeeds in compiling its identity to Firebase and both hardware and software can interact on a pervasive basis.